Pengaruh Struktur Modal, Ukuran Perusahaan dan Agency Cost Terhadap Financial Distress Pada Perusahaan Sub Sektor Otomotif Periode 2020-2024 - Aldi Setiawan; Ina Liswanty; Emi Masyitah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to determine the effect of capital structure, company size, and agency costs on financial distress in companies in the automotive sub-sector during the 2020-2024 period. This study employed quantitative research. Secondary data sources were used. The population consisted of 10 companies, with a sample size of 50. Data analysis techniques used included descriptive statistical analysis, classical assumption tests, hypothesis testing, and coefficient of determination tests. Based on the partial t-test results, it can be seen that capital structure does not significantly influence financial distress, with a calculated t-value of -1.174 < 2.012. Furthermore, company size does not have a positive and significant effect on financial distress, with a calculated t-value of -1.737 < 2.012. Agency costs do not have a positive and significant effect on financial distress, with a value of -1.737 < 2.012. Based on the simultaneous test, the calculated F value is 75.490 with a significance level of 0.000. If calculated F > F table, there is a significant influence between X1, X2, and X3 on Y.